CHEMICAL CONTENT AND ANATOMICAL CHARACTERISTICS OF SAGO (Metroxylon sagu Rottb.) FROND FROM SOUTH KALIMANTAN, INDONESIA - Wiwin Tyas Istikowati; Sunardi; Budi Sutiya; Purnama Lestari; Ahmad Arsyad; Lusyiani; Danang Sudarwoko Adi; Widya Fatriasari; Riska Surya Ningrum; Dede Heri Yuli Yanto (APTKLHI, 2023)
This research aims to evaluate the suitability of sago palm waste as a fiber raw material in terms of its chemical content and anatomical characteristics. The chemical content analysis of its extractive components, lignin, holocellulose, α-cellulose, and hemicellulose, was carried out using sago frond powder with a size of 40–60 mesh. Subsequently, functional group analysis was performed using Fourier Transform Infra-Red (FTIR), while anatomical characterization was carried out by calculating the fiber length and diameter, lumen diameter, fiber derivative values, and wall thickness using a microscope connected to a digital camera. Scanning Electron Microscope (SEM) pictures were taken in different magnifications. The results showed that sago frond contains 31.6% α-cellulose and 38% lignin. The α-cellulose content was within the standard range for non-timber forest products, but the lignin content had a relatively high value. Based on the derived value, namely class II, sago frond can be used as pulp and paper raw materials.